The Bible and Medieval Culture - Lourdaux, W. (Mediaevalia Lovaniensia - Series 1/Studia, 1984)
From May 16th to 19th 1977, philologist, historians, sociologists, philosophers and theologians gathered in Louvain, to attend the Vllth International Colloquium organized by the 'Instituut voor Middeleeuwse Studies' of the 'Katholieke Universiteit te Leuven', to discuss and investigate the influence of the Bible on medieval culture. It is indisputable that medieval society in its various aspects was deeply penetrated and strongly influenced by the Bible. Many important studies have already been published on this subject, but the organizers of the Colloquium recognized that much further work was still required, and focussed attention on three fundamental problems, to which the attention of participants was directed. Firstly, some centuries passed before the Bible was translated into vernacular languages, as a result of the Church's policy that the Bible should only be read in one of the 'sacred languages' - Hebrew, Greek or Latin. The vulgate version for Western christendom was St Jerome's Latin translation, but a stimulus and demand gradually grew for vernacular translations. In the course of the 9th century, the Frankish Otfrid of Weissenburg raised the significant question whether the language of the Franks was indeed to trivial or inferior that it was worthless or useless for speaking to God. But the Church was reluctant to permit the Bible to be translated into the common tongues, through fear of the confusion and uncertainty which might result for uneducated people. Nevertheless, and secondly, in spite of many obstacles, such translations in fact appeared, principally in German, Anglo-Saxon, French and Dutch. And thirtly, in consequence of these developments, the Bible impacted a specific outlook to medieval society, and the translators recorded in their versions the contemporary customs and habits of their people. The Bible translations created a new vocabulary, and the translators used their own language and idioms to render the Bible stories more lively and comprehensible. The various contributions to the International Colloquium dealt with these three themes, as well as other aspects of medieval life on which the Bible left its mark.